High-sensitivity, fast-response flexible pressure sensor for electronic skin using direct writing printing. Issue 44 (13th July 2020) - Chen, Xiaojun; Lin, Xitong; Mo, Deyun; Xia, Xiaoqun; Gong, Manfeng; Lian, Haishan; Luo, Yihui
Abstract : Bionic electronic skin with human sensory capabilities has attracted extensive research interest, which has been applied in the fields of medical health diagnosis, wearable electronics, human–computer interaction, and bionic prosthetics. Abstract : Bionic electronic skin with human sensory capabilities has attracted extensive research interest, which has been applied in the fields of medical health diagnosis, wearable electronics, human–computer interaction, and bionic prosthetics. Electronic skin tactile pressure sensing required high sensitivity, good resolution and fast response for sensing different pressure stimuli. In particular, there were still great challenges in the detection of wide pressure and the preparation of sensitive unit microstructures. Here, the direct-write printing of Weissenberg principle to fabricate GNPs/MWCNT filled conductive composite flexible pressure sensors on PDMS substrates was proposed. The effects of platform moving speed, microneedle rotation speed and the number of direct-write times on the line width of the pressure sensitive structure were investigated based on orthogonal experiments, and the optimal direct-write printing parameters were obtained. The performance of the S-shaped polyline pressure sensor was tested, in which the sensitivity could reached 0.164 kPa −1, and the response/recovery time was 100 ms and 100 ms respectively. The capture cases of objects of different quality and objects with flat/curved surfaces were successively demonstrated to exhibit its excellent sensitivity, stability and fast response performance. This work may paved the road for future integration of high-performance electronic skin in smart robotics and prosthetic solutions.